PENGARUH RASIO KINERJA KEUANGAN TERHADAP PROFITABILITAS PADA BANK UMUM SYARIAH DI INDONESIA PERIODE 2009-2018 - Ulfa Noviana; Israk Ahmadsyah; Ana Fitria (Jurnal Ekonomi & Perbankan Syariah, 2021)
ROA ratio is a ratio that measures a bank's ability to generate overall profits. ROA high and low depends on the management of the company's assets by management. The higher the ROA the more efficient the company's operations and rather, the lower ROA can be caused by several factors that influence it, one of which is the company's internal factors. This study aims to see the effect of Capital Adequacy Ratio (CAR), Performing Financing (NPF) and Financing to Deposit Ratio (FDR) on Return On Assets (ROA). The method used is quantitative with the sample in this study were 5 Islamic commercial banks in Indonesia. Research that uses a combined panel data regression model from time series and cross section data with the chosen approach is the Fixed Effect Model (FEM). Data processing using the Eviews 9 program. The results of the research that have been conducted show that simultaneously the CAR, NPF and FDR variables affect the ROA of Islamic Commercial Banks. Partially the CAR and FDR variables have no significant effect on ROA and NPF have a negative and significant effect on ROA. The coefficient of determination (R2) is 0.515 which indicates that the effect of the independent variables (CAR, NPF and FDR) on ROA is 51.5% while the remaining 48.5% is due to other factors outside the panel data regression model studied. For the Islamic Commercial Banks in Indonesia, they are able to optimize available capital to the maximum in order to increase bank profitability, reduce the NPF ratio in non-performing financing and increase FDR in channeling funds effectively so that the resulting profitability will be maximized.Keywords: ROA, CAR, NPF, FDR and Islamic Bank.